Nutrition Counseling Need in Burn Patients - Kiki Lukman; Hardisiswo Soedjana; Rani Septrina; Lisa Hasibuan; Selvy Harianti; Amelia Febrina (Faculty of Medicine, Universitas Padjadjaran, 2020)
Burns can increase metabolic responses of the sufferers, making adequate nutrition important for burn patients and needs to be considered in the management of burns. Counseling on the importance of nutrition for burn patients can reduce the risk of burn complications. This study was an intervention study designed to increase the community's knowledge and awareness of the importance of nutrition in burn patients. In this study, a lecture session and discussion session on nutrition in burn patients were held by the Division of Plastic Surgery, Department of Surgery, Dr. Hasan Sadikin General Hospital, Bandung, Indonesia at the Jatinangor Public Health Center, Sumedang, Indonesia, on August 14, 2019. Of all participants attending this event, thirty-one participants who participated in through the whole agenda of this event were sampled to be the respondents. Data were collected using a pre- and post-test questionnaires consisting of items on basic knowledge, first treatment, and nutrition for burn patients. More women (74%) participated in this study. Most respondents were over 40 years old (39%) and graduated from senior high school (39%). There was a significant increase in knowledge of the respondents before and after counseling the nutrition of burn patients (p<0.05). Thus, counseling is proven to increase knowledge in the general population that it should be performed routinely in various areas. Perlunya Penyuluhan Nutrisi Pada Pasien Luka Bakar Luka bakar dapat meningkatkan respons metabolik penderitanya. Nutrisi adekuat pada pasien luka bakar merupakan hal yang cukup penting dan perlu diperhatikan dalam penatalaksanaan luka bakar. Penyuluhan tentang pentingnya nutrisi untuk pasien luka bakar dapat mengurangi risiko komplikasi luka bakar. Penelitian ini adalah studi intervensi yang dirancang untuk meningkatkan pengetahuan dan kesadaran masyarakat tentang pentingnya nutrisi pada pasien luka bakar. Dalam penelitian ini, sesi kuliah dan sesi diskusi tentang nutrisi pada pasien luka bakar diadakan oleh Divisi Bedah Plastik, Departemen Bedah, Rumah Sakit Umum Dr. Hasan Sadikin, Bandung, Indonesia di Pusat Kesehatan Masyarakat Jatinangor, Sumedang, Indonesia, pada 14 Agustus 2019. Dari semua peserta yang menghadiri acara ini, tiga puluh satu peserta yang berpartisipasi melalui seluruh agenda acara ini dijadikan sampel untuk menjadi responden. Data dikumpulkan menggunakan kuesioner sebelum dan sesudah tes yang terdiri atas pengetahuan dasar, pengobatan pertama, dan nutrisi untuk pasien luka bakar. Lebih banyak perempuan (74%) yang berpartisipasi dalam penelitian ini. Sebagian besar responden berusia di atas 40 tahun (39%) dan lulus dari sekolah menengah atas (39%). Ada peningkatan yang signifikan dalam pengetahuan responden sebelum dan sesudah penyuluhan nutrisi pasien luka bakar (p<0,05). Simpulan, penyuluhan terbukti meningkatkan pengetahuan masyarakat bahwa itu harus dilakukan secara rutin di berbagai bidang.